Preservatives to enhance shelf life and Quality of kinnow juice stored under Refrigerated condition - ANIL DHAKA,; MADHU SHARMA,; SHAILESH KUMAR SINGH, (International Journal of Pharma and Bio Sciences, 2016)
Kinnow (Citrus nobilis × Citrus deliciosa L.) is a widely grown Citrus species known for its high quality fruit juice with good storage life. The present investigation is concerned with the enhancement of shelf-life of Kinnow fruit juice through refrigeration storage and addition of preservatives. Fruit juice was prepared from fruits harvested at complete physiological maturity and potassium meta-bisulphite or sodium benzoate alone or in combination were added as preservatives to enhance shelf life of fruit juice. Further, bottled fruit juices were stored under refrigerator and quality was evaluated at 15 days interval for 45 days. The experimental findings showed that TSS, ascorbic acid, reducing sugar and total sugar were increased up to 45 days of storage and maximum value was reported in T6 (13.27oBrix, 29.33mg/100ml, 3.61% and 8.01%, respectively) followed by T8 (12.87oBrix, 28.67mg/100ml, 3.57% and 7.97%, respectively) at 45 days of storage while titrable acidity ranged from 1.17 to 1.18 % for different treatments in comparison to untreated juice (1.21%). The minimum absorbance at 440 nm wavelength was reported in T6 (0.086-0.091) while microbial count was minimum in T7 (2.58 x 103 - 1.30 x 105). The investigation clearly revealed that the shelf-life of Kinnow juice can be extended up to 45 days without qualitative loss when 0.05 % of potassium meta-bisulphite or 0.05% of sodium benzoate were added alone or in combination.